Comparison of Amniotic Membrane Transplantation and Conjunctival Autograft Transplantation for the Treatment of Pterygium - Fatemeh Eslami (پزشکی بالینی ابن سینا, 2019)
Background and Objective: Pterygium is a fibrovascular and wedge-shaped lesion that extends from bulbar conjunctiva to the cornea. Pathogenesis of pterygium depends on several factors and sunlight exposure is an important risk factor for this syndrome. Surgery is regarded as the key to successful treatment of pterygium. With this background in mind, the aim of this study was to determine the effect of amniotic membrane transplantation (AMT) for the treatment of pterygium. Moreover, this technique was compared clinically with conjunctival autograft transplantation (CAT). Materials and Methods: In this randomized clinical trial, 70 patients either referred to the ophthalmologic clinic of Farshchian Hospital in Hamadan, Iran, or diagnosed by an ophthalmologist with primary or recurrent pterygium were enrolled in this study. The patients were randomly divided into two groups, (n=35). One group underwent pterygium surgery using AMT and the other one was subjected to CAT. Furthermore, the inflammation and recurrence rates after surgery were compared in both groups. Data were analyzed in SPSS software (Version16) through the Chi-square and the independent sample t-tests. Results: According to the results, the mean ages of patients in the AMT and CAT groups were 47.34±14.85 and 48.26±15.26 years, respectively (P=0.778). Moreover, inflammation was observed in 28.6% and 8.6% of patients in the AMT and CAT groups, respectively. The recurrence rates were 22.9% and 11.4% in the AMT group and CAT group, respectively (P=0.205) Conclusion: The AMT had a higher recurrence rate and postoperative inflammation, compared to the CAT. Although this difference was not statistically significant, the CAT is widely used as a treatment for patients with pterygium.